Disaster resilience – a challenged science. (1st January 2020) - Parker, Dennis J.
ABSTRACT: The concept of resilience has become prominent and now dominates thinking about risk management, notably including environmental hazard management. This paper examines the diverse origins of resilience and its conceptual roots within the hazard and disaster management field and then questions whether or not resilience is simply a re-branding of the concept of mitigation which has previously been widely employed in the hazard and disaster management field. The discussion leads to the conclusion that resilience is not a simple re-branding but is a concept that goes well beyond mitigation to embrace adaptation, change and transformation. Whether disaster resilience is a mature science is discussed next, providing evidence that it is not yet mature because there is currently no settled definitional, conceptual or theoretical basis for the science which is widely recognised and adhered to. Finally, the significant challenges that disaster science has in becoming a more mature and readily applicable science are discussed before the six papers in this Special Issue are introduced.